2003
DOI: 10.1159/000072430
|View full text |Cite
|
Sign up to set email alerts
|

TT Virus Infection Does Not Affect the Clinical Profiles of Patients with Hepatitis B and C in Yanbian City, China

Abstract: China is an area of high endemicity for viral hepatitis, and the molecular epidemiological investigation of TT virus (TTV) infection is of interest. In the present study, we investigated the epidemiology, clinical significance and molecular characteristics of TTV infection in patients with chronic hepatitis B and C in Yanbian City, China. Serum samples obtained from 74 patients with hepatitis B and hepatitis C who visited Yanbian Hospital, located in northeast China, were analyzed in this study. The study grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We are therefore in agreement with previous observations that TTV infection does not seem to be related to abnormal ALT levels, and ALT abnormality was mainly attributable to HCV, HBV or HGV and not TTV infection. 38 , 39 The presence or absence of serum TTV DNA does not seem to affect the clinical course of patients with chronic HBV or HCV infection and TTV viremia with any genotype was not associated with HBV, HCV or HGV infection and abnormal ALT levels. 40 , 41 …”
Section: Discussionmentioning
confidence: 98%
“…We are therefore in agreement with previous observations that TTV infection does not seem to be related to abnormal ALT levels, and ALT abnormality was mainly attributable to HCV, HBV or HGV and not TTV infection. 38 , 39 The presence or absence of serum TTV DNA does not seem to affect the clinical course of patients with chronic HBV or HCV infection and TTV viremia with any genotype was not associated with HBV, HCV or HGV infection and abnormal ALT levels. 40 , 41 …”
Section: Discussionmentioning
confidence: 98%
“…It was found that TTV co-infection had little or no effect on severity of biochemical parameters of liver damage in hepatitis C patients. Zhao et al 14 and Moriyama et al 15 reported that TTV co-infection did not modify the serology or biochemical markers of chronic hepatitis B and C. However, few workers have reported increased severity of biochemical and histologic parameters of liver damage in hepatitis C patients co-infected with TTV. 16 In our study, TTV viraemia was associated with raised serum bilirubin, AST, ALT and alkaline phosphatase levels in only 1%, 2%, 4% and 1% healthy individuals respectively.…”
Section: [ ( F I G _ 3 ) T D $ F I G ]mentioning
confidence: 99%
“…TTV were originally isolated from a patient suffering from posttransfusion hepatitis (35), but a direct role in the pathogenesis of this disease or in hepatocellular carcinoma has not been established (31,32,46). Several studies have failed to demonstrate a direct association of TTV with lymphomas and myelomas (2,8,60).…”
mentioning
confidence: 99%